Ultrasound-Assisted Extraction of Anthocyanins from Malus ‘Royalty’ Fruits: Optimization, Separation, and Antitumor Activity - Yixin Liu; Yuheng Zhao; Yue Zhuo; Yuwen Li; Jiaxin Meng; Yilin Wang; Houhua Li (Molecules, 2022)
Red Malus ‘Royalty’ fruits are rich in anthocyanins. This study aimed to obtain the optimal parameters for the extraction and separation of anthocyanins from Malus ‘Royalty’ fruits and to evaluate the inhibitory effect of the enriched anthocyanin fraction on gastric cancer cells. Ultrasonic-assisted extraction was used for the extraction of the anthocyanins of Malus ‘Royalty’ fruit, and the extraction results showed that the optimum parameters were an extraction temperature of 20 °C, a solid–liquid ratio of 1:6 (g/mL), ethanol and formic acid contents of 70% and 0.4%, respectively, an extraction time of 40 min, and an ultrasonic power of 300 W. The optimum extraction parameters to achieve the highest anthocyanin yield by a single-factor experiment coupled with response surface methodology were identified. The separation results showed that the AB-8 macroporous resin was a better purifying material, with 60% ethanol as an adsorbent, and the adsorption–desorption equilibrium times were 6 h and 1 h, respectively. Cyanidin-3-galactoside was the main body composition separation of anthocyanins by a high-performance liquid chromatography-diode array detector. The antitumor activity results showed that the anthocyanins of Malus ‘Royalty’ fruits have a significant inhibitory effect on the gastric cancer cell line BGC-803. The in vitro cell viability test of CCK-8 showed that the inhibitory effect on tumor cells was more significant with the increased anthocyanin concentration, with a half maximal inhibitory concentration (IC50) value of 105.5 μg/mL. The cell morphology was observed by an inverted microscope, and it was found that the backbone of BGC-803 treated with a high concentration of anthocyanins was disintegrated and the nucleoplasm was concentrated. The mechanism of apoptosis was analyzed by Western blotting, and the results showed that with increasing anthocyanin concentration in the medium, the expression levels of the proapoptotic proteins Bax and Bak increased, and the expression levels of the antiapoptotic proteins Bcl-2 and Bcl-xL decreased, which coordinated the regulation of cell apoptosis. This research suggests that the enriched anthocyanin fraction from Malus ‘Royalty’ fruits have potential antitumor and adjuvant therapeutic effects on gastric cancer.